Microwave-assisted co-precipitation preparation of CuFe2O4 photo-Fenton degradation tetracycline: Characterization, efficacy, stability in complex water quality and mechanism. Issue 1 (February 2023) - Sun, Xiyu; Wang, Guangzhi; Huang, Likun; Feng, Huanzhang; Zhou, Simin; Zhao, Rui; Wang, Dongdong; Li, Zhe
Abstract: A magnetic copper ferrite (CuFe2 O4 ) photocatalyst was successfully synthesized by the modified microwave-assisted co-precipitation method to improve the removal performance of tetracycline (TC) and the reusability of a photocatalyst. A series of tests indicate that microwaves could reach the inside of the material quickly and uniformly with its energy so that CuFe2 O4 exhibited a more significant specific surface area, magnetic intensity, and separation efficiency of photogenerated electron-hole pairs. CuFe2 O4 reached superior photo-Fenton performance of TC in the presence of Cl -, NO3 –, HCO3 –, HPO4 2–, SO4 2– and humic acid, as well as deionized water, river water, and secondary effluent. Ten recycling tests in these three different water quality backgrounds confirmed the stability and remarkable activity of CuFe2 O4, with the removal rate only decreasing by 2.0 %, 1.5 %, and 2.1 %, respectively. Free radical capture experiments as well as electron spin resonance suggest that·OH and O2 · - were mainly involved in the degradation of TC, and the photo-Fenton degradation mechanism and equations were proposed. Toxicity evaluation declared that CuFe2 O4 photo-Fenton degradation of TC was a safe and promising technology. This study offered prospects of magnetic CuFe2 O4 prepared by the modified microwave-assisted co-precipitation method in TC wastewater treatment. Graphical Abstract: ga1 Highlights: CuFe2 O4 was constructed by the modified microwave-assisted co-precipitation method. Microwave assistance significantly enhanced the performance of CuFe2 O4 . CuFe2 O4 exhibited efficient tetracycline removal in the presence of anions. CuFe2 O4 exhibited efficient tetracycline removal under different water quality. Excellent magnetic properties of CuFe2 O4 facilitated its separation and recycling.